2021
DOI: 10.1007/s00280-021-04302-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic physiology-based pharmacokinetic modeling to elucidate vincristine-induced peripheral neuropathy following treatment with novel kinase inhibitors

Abstract: Purpose Limited information is available regarding the drug–drug interaction (DDI) potential of molecular targeted agents and rituximab plus cyclophosphamide, doxorubicin (hydroxydaunorubicin), vincristine (Oncovin), and prednisone (R-CHOP) therapy. The addition of the Bruton tyrosine kinase (BTK) inhibitor ibrutinib to R-CHOP therapy results in increased toxicity versus R-CHOP alone, including higher incidence of peripheral neuropathy. Vincristine is a substrate of P-glycoprotein (P-gp, ABCB1); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A potential connection of ABCB1mediated efflux and vincristine toxicity is supported by the previous finding that variants in the ABCB1 gene are correlated with VIPN in some populations (Pozzi et al, 2021). Interestingly, studies involving physiology-based pharmacokinetic modeling of vincristine (Pilla Reddy et al, 2021) and the use of knockout mice (Wang et al, 2010) have suggested that pharmacological inhibition or genetic deficiency of ABCB1 is associated with negligible increases in the plasma concentrations of vincristine. Although further validation studies are required under ABCB1deficient conditions and to determine the potential for drug-drug-gene interactions (Malki and Pearson, 2020), this collective prior work implies that modulation of ABCB1 in target cells within the peripheral nervous system can affect the cellular retention of vincristine and downstream toxic events without altering systemic clearance (Stage et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…A potential connection of ABCB1mediated efflux and vincristine toxicity is supported by the previous finding that variants in the ABCB1 gene are correlated with VIPN in some populations (Pozzi et al, 2021). Interestingly, studies involving physiology-based pharmacokinetic modeling of vincristine (Pilla Reddy et al, 2021) and the use of knockout mice (Wang et al, 2010) have suggested that pharmacological inhibition or genetic deficiency of ABCB1 is associated with negligible increases in the plasma concentrations of vincristine. Although further validation studies are required under ABCB1deficient conditions and to determine the potential for drug-drug-gene interactions (Malki and Pearson, 2020), this collective prior work implies that modulation of ABCB1 in target cells within the peripheral nervous system can affect the cellular retention of vincristine and downstream toxic events without altering systemic clearance (Stage et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…An example of such an approach is the recently published PBPK model for vincristine and its application to predict potential drug–drug interactions with Bruton tyrosine kinase inhibitors being added to R‐CHOP protocols for lymphoma. 25 ABCB1 activity is of particular concern in veterinary medicine as the frequency and variability of canines presenting the ABCB1‐1Δ 61 mutation necessitates further understanding of its implications in the context of VBL treatment. Although VBL PK levels in all other tissues are not significantly different between the wild‐type and Mdr1a/b(−/−) mouse data, the presence of a known mutation in a clinical setting can have implications on achieved VBL plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This model provides the quantitative framework to test and validate potential drug–drug interactions and extrapolate to individual physiological conditions such as diminished liver or renal function. An example of such an approach is the recently published PBPK model for vincristine and its application to predict potential drug–drug interactions with Bruton tyrosine kinase inhibitors being added to R‐CHOP protocols for lymphoma 25 . ABCB1 activity is of particular concern in veterinary medicine as the frequency and variability of canines presenting the ABCB1‐1Δ 61 mutation necessitates further understanding of its implications in the context of VBL treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations